THE IMPACT OF FINANCIAL INNOVATION ON MARKET RELATIONS BETWEEN BITCOIN AND OIL - KOTVYTSKA, Nataliia; SKLIARENKO Оlena; SHAROVA, Svitlana; SHCHERBATYKH, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This paper examines the relationship between Bitcoin and oil markets through multiple instruments, including WTI futures, Brent futures, E-mini futures, and the United States Oil Fund ETF (USO), spanning from 2020 to mid 2024. Using cointegration analysis, correlation metrics, and volatility measures, we find distinct patterns across different oil market instruments. While direct oil futures show no significant cointegration with Bitcoin, the USO ETF exhibits weak cointegration despite having the lowest correlation (0.2952) among all instruments studied. Our volatility analysis reveals that USO demonstrates lower volatility (0.3761) compared to both WTI futures (0.6294) and Bitcoin (0.6107), suggesting a dampening effect of retail-oriented financial products. The correlation analysis shows moderate positive relationships between Bitcoin and oil futures (0.38), but these relationships vary considerably over time and across instruments. Our findings indicate that the way investors access oil markets significantly influences the asset’s relationship with Bitcoin, highlighting the importance of financial product structure in cross-market dynamics. These results have important implications for portfolio diversification, risk management, and market structure analysis in an era of increasing integration between traditional and digital financial markets. The study contributes to the understanding of how financial innovation affects relationships between cryptocurrency and commodity markets, suggesting that market access points matter as much as underlying asset relationships.